The Modeling of Transportation and Transport Processes of a Territory Administration Region - Hollarek, Tomas; Molnar, Imrich; Palo, Jozef (Communications - Scientific letters of the University of Zilina, 2002)
The development of transport caused the rise of complex transport problems, which require the application of transport engineering methods if they are to be solved. The modeling of transportation and transport processes in major territory units is a current problem for the reason of completing the road and motorway networks and considering individual variants of the solution. Recently, new transport planning models have been formulated on the principle of dividing the inhabitants into the groups with similar behavior in the transport process. They are called non-aggregative or individual, and one of the aims of the research project was to test these models in the region of Žilina, and to compare the results with the aggregative models which have been used so far and which are different only in the list of requirements for transfer.